PROBLEMATICAL ASPECTS OF APPLICATION OF MATCHING PRINCIPLE FOR THE PURPOSE OF LEGAL ENTITIES TAXATION ON CORPORATE INCOME TAX - Endrijaitis, Martynas (Teisė, 2016)
The article discloses the meaning, substance of the matching principle. Analysis is performed to discuss if comparison between costs and income is self-dependent principle or just one of conditions based on application of accrual principle for the purpose of legal entities taxation on corporate income tax. Consequently, there are analyzed other application of the matching principle aspects.